Treatment and enhanced degradation of petrochemical wastewater by continuous stirred tank reactor - Siddique, Md. Nurul Islam (2012)
Currently, the world is facing two coexisting problems-1) the proper management of wastes generating from the industrial sectors, and 2) the scarcity for novel resources of gasoline to meet up energy demand of civilization. Anaerobic codigestion, a sustainable green technology presents an outstanding opportunity both for energy conversion and pollution control. It has a wide variety of applications treating numerous wastewaters such as agro-agricultural, industrial, municipal, domestic sewage etc. Therefore, it has become a core method with meticulous attraction treating organic wastes on account of its economic benefits of energy generation. The continuous stirred tank reactor (CSTR) can be defined as a sealed-tank digester equipped with mixing facility. Chemical pretreatment coupled with anaerobic co-digestion technology was applied on petrochemical wastewater using CSTR focusing on enhanced hydrolysis and methanogenesis. Particularly, batch experiments were performed, with applied H2O2 doses of 0.5, 1 and 1.5% for contact times of 5, 10 and 15 min. Results revealed that 1% H2O2 dose (1.0mM Fe3+2) for 5 min exposure elevated biodegradability index (BOD/COD) up to 35%. Catalase activity scavenged the toxicity on microbes. Subsequently, batch experiments were employed, with various mixing proportions of petrochemical wastewater (PWW): dairy cattle manure (DCM): beef cattle manure (BCM), such as 25: 37: 38, 40: 30: 30, 50: 25: 25, 60: 20: 20, and 75: 12: 13. Results revealed that PWW: DCM: BCM ratio (50: 25: 25) provided maximum methane production. Hence, CSTR was operated with this specific feed ratio. Effect of temperature and organic loading was also verified. Batch test operation was also performed for ammonium bicarbonate (NH4HCO) dosing avoiding volatile fatty acid (VFA) accumulation. Specific dosing limit was selected up to 40 mg/L. A 10 mg/L of NH4HCO3 3 dosing was proved suitable. Although methane production is considered to get introverted by VFA accumulation leading to reactor instability during anaerobic digestion, the co-digestion of PWW together with BCM and DCM caused 50% enhancement in methane production, followed by a 98±0.5% reduction in chemical oxygen demand at 10 days hydraulic retention time. No VFA buildup was identified, demonstrating that reactors were not running at stress-overloading situations. In comparison with the digestion of PWW alone, methane yield increased by 50–60% under mesophilic conditions and 50–65% under thermophilic conditions due to codigestion. This was induced by an optimum C: N ratio (30:1) of the feed stock ensuring microbial growth and buffering capacity. This study provides guidelines for kinetic analysis of the viability of transforming PWW to bioenergy.